The influence of risk perception in mountaineering on re-participation intentions: a moderated mediation model - Gu, Huihui; Zhao, Qi; Liu, Ye; Yin, Yutong; Bai, Shengchao (Frontiers in Psychology, 2026)
ObjectiveMountaineering is a high-risk outdoor activity requiring strong psychological regulation and risk assessment abilities. The study aims to investigate the relationship between risk perception in mountaineering and re-participation intention, specifically focusing on the mediating role of smooth experience and the moderating effect of social support.MethodsDrawing on Risk Perception Theory and Flow Theory, we proposed a moderated mediation model and surveyed 516 recreational mountaineering participants. Descriptive statistics, reliability and validity tests, and moderated mediation analyses were conducted using SPSS 27.0 (PROCESS 4.1, 5,000 bootstrap resamples).Results(1) Risk perception negatively predicted both re-participation intention and smooth experience. (2) Smooth experience positively predicted re-participation intention and mediated the association between risk perception and re-participation intention. (3) Social support moderated the smooth experience and re-participation intention link, such that the positive effect of smooth experience was stronger at higher levels of social support.ConclusionSmooth experience constitutes a key psychological pathway through which risk perception relates to re-participation intention, and social support strengthens the behavioral benefits of smooth experience. These findings highlight the joint role of psychological experience and social resources in promoting sustained engagement in mountaineering.